Effect of exercise preconditioning on myocardial content of Sphingosine1-phosphate and its mechanism in rats after exhaustive exercise - Xinnuan Wei; Weiyuan Yang; Junxiang Zhou; Luoyuan Cao; Wenxing Jiang (PLoS ONE, 2026)
Objective This study aimed to investigate the effects of exercise preconditioning on rat myocardial Sphingosine1-phosphate(S1P) content and its potential mechanisms of heart protection. Methods A rat model of exercise preconditioning followed by exhaustive exercise was established. Rats were randomized to four groups: control (C), exercise preconditioning (EP), EP plus the S1PR1-selective antagonist W146 (EP + W146), and EP plus the MEK1/2 inhibitor PD98059 (EP + PD98059). Following a final exhaustive swim, comparisons across groups revealed that EP attenuated myocardial injury and apoptosis, an effect which was abolished by both W146 and PD98059. Results 1. Exercise preconditioning (EP) significantly attenuated exhaustive exercise-induced myocardial injury and apoptosis ( P < 0.001); 2. EP significantly elevated myocardial S1P levels ( P = 0.002), and S1PR1-selective antagonist (W146) abolished this cardioprotective effect ( P = 0.016 for apoptosis); 3. Most importantly, MAPK pathway inhibition (PD98059) abrogated the protective effect of EP, as evidenced by significantly increased apoptosis ( P = 0.002), despite unaltered S1P levels. Conclusion In summary, beyond confirming S1P elevation with exercise preconditioning, our findings propose the S1P→MAPK signaling axis as a novel mechanistic pathway warranting future validation.